2022
DOI: 10.3390/brainsci12080994
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Interventions Combined with Noninvasive Brain Stimulation on Upper Limb Motor Function in Stroke Patients

Abstract: (1) Background: This systematic review aimed to focus on the effects of rehabilitation interventions combined with noninvasive brain stimulation on upper limb motor function in stroke patients. (2) Methods: PubMed, MEDLINE, and CINAHL were used for the literature research. Articles were searched using the following terms: “Stroke OR CVA OR cerebrovascular accident” AND “upper limb OR upper extremity” AND “NIBS OR Non-Invasive Brain Stimulation” OR “rTMS” OR “repetitive transcranial magnetic stimulation” OR “tD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…One could argue that NIBS could also have positive effects when coupled with conventional therapy. Actually, several works assessed NIBS coupled with conventional physiotherapy as compared to stand-alone for either upper or lower limbs, showing the coupled intervention as an effective strategy to improve motor function recovery in post-stroke patients [ 2 , 87 ]. No studies directly compared RAR, NIBS, and conventional physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that NIBS could also have positive effects when coupled with conventional therapy. Actually, several works assessed NIBS coupled with conventional physiotherapy as compared to stand-alone for either upper or lower limbs, showing the coupled intervention as an effective strategy to improve motor function recovery in post-stroke patients [ 2 , 87 ]. No studies directly compared RAR, NIBS, and conventional physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since late 1990s, applications of TMS on neurological rehabilitation and treatment of different neurological diseases have been the focus of researches. TMS on motor rehabilitation and dysphasia is gaining more and more support from evidences in literature [7][8][9][10]. With advancement in technology, introduction of navigated TMS provides more precise application of TMS in mapping and treatment.…”
Section: Historymentioning
confidence: 99%
“…Noninvasive brain stimulation can modify cortical excitability and improve behavioral performance by regulating brain electrical activity. Several studies have also suggested the effectiveness of combining noninvasive brain stimulation with other therapies to enhance upper limb motor impairment (3)(4)(5). According to estimates, the application of repetitive transcranial magnetic stimulation (rTMS) could potentially lead to a 10-20% improvement in upper limb motor function after five sessions (6).…”
Section: Introductionmentioning
confidence: 99%